Isolation, identification, and genomic analysis of bacteriophage GJKY-A for the prevention and treatment of citrus canker - Wu, Yang; Li, Zexia; Li, Kexin; Li, Weiwei; Chang, Mingxue; Liu, Dingkun; Hu, Songjia; He, Li; Sun, Huimin (Frontiers in Microbiology, 2025)
IntroductionCitrus canker, caused by Xanthomonas citri subsp. citri (Xcc), leads to severe economic losses in global citrus production. Conventional chemical control strategies are increasingly hindered by bacterial resistance and environmental concerns. Bacteriophages offer a sustainable alternative for plant disease management.MethodsThis study isolated bacteriophages from wastewater using a double-layer plate method, and conducted biological characterization and genomic analysis on the isolated bacteriophages.ResultsWe report the isolation and characterization of a phage, GJKY-A, from sewage effluent targeting Xcc. Transmission electron microscopy revealed an polyhedral head (~90 nm) and a long, flexible non-contractile tail (~150 nm). One-step growth analysis showed a latent period of 20 min and a burst size of ~84 plaque-forming units per cell. GJKY-A displayed high host specificity and remained stable across 40–50 °C and pH 3–12. Genomic sequencing identified a 62,551 bp double-stranded DNA genome with 44.81% GC content. Analysis of the taxonomic status of the phage shows that phage GJKY-A is closely related to phages of the genus Stenotrophomonas. Functional assays demonstrated efficient inhibition of host growth in vitro and suppression of citrus canker symptoms in ex vivo leaf assays.DiscussionThese findings establish GJKY-A as a promising biocontrol candidate and provide a foundation for developing safe, eco-friendly strategies for citrus canker management.